Gut Mucosal Antibody Responses and Implications for Food Allergy - Hoh, Ramona A.; Boyd, Scott D. (Frontiers in Immunology, 2018)
The gastrointestinal mucosa is a critical environmental interface where plasma cells and B cells are exposed to orally-ingested antigens such as food allergen proteins. It is unclear how the development of B cells and plasma cells in the gastrointestinal mucosa differs between healthy humans and those with food allergy, and how B cells contribute to, or are affected by, the breakdown of oral tolerance. In particular, the antibody gene repertoires associated with symptomatic allergy have only begun to be characterized in full molecular detail. Here, we review literature concerning B cells and plasma cells in the gastrointestinal system in the context of food allergy, with a focus on human studies.